007 The tumour suppressor Ras-association domain family 1 isoform A (RASSF1A): a novel modulator of hypertrophic signalling pathway in the heart. (22nd September 2015) - Oceandy, D; Pickard, A; Mohamed, T; Zi, M; Prehar, S; Cartwright, E; Neyses, L
Abstract : Myocardial hypertrophy is an important pathological process that can lead to heart failure, therefore understanding the molecular mechanisms of cardiac hypertrophy is key in elucidating the pathogenesis of this disease. One important signalling pathway which has been associated with cardiac hypertrophy is the Ras pathway. It is known that mutations in genes of the Ras signalling pathway are associated with syndromes (eg, Noonan and Costelloe) that are characterised by tumour formation and cardiac hypertrophy. This lead us to hypothesise that negative regulators of the Ras pathway may also limit cardiac growth in common conditions such as pressure overload. One such negative regulator of tumour growth is the recently described tumour suppressor protein RASSF1A (Ras-association domain family 1 isoform A). Although we and others have detected RASSF1A expression in the heart, little is known about its functions. Here we investigate the role of this molecule in regulating myocardial hypertrophy. We used mice with genetic ablation of the Rassf1a gene and isolated neonatal rat cardiomyocytes with adenoviral mediated overexpression of RASSF1A to investigate the role of RASSF1A in the heart. Induction of pressure overload hypertrophy by transverse aortic constriction (TAC) resulted in enhanced myocardial hypertrophy in knock out (KO) mice compared to wild type (WT) controls (64.7% increase in heart weight/body weight ratio in RASSF1A KO mice compared to 30.6% in WT, n=10, p<0.05). Histological analysis showed that TAC-stimulated RASSF1A KO mice exhibited a significant increase in cross sectional myocyte area (121% increase in KO vs 22% increase in WT (p<0.01)) and fibrosis (22% fibrosis area in KO vs 11% in WT, p<0.01). This was accompanied by an increased expression of hypertrophic markers (BNP and ANP) in KO mice. Consistent with the in vivo data, overexpression of human RASSF1A in neonatal rat cardiomyocytes markedly reduced the cellular hypertrophic response to phenylephrine stimulation by ∼50% compared to control cells as indicated by analyses of cell size, protein synthesis and BNP expression. In addition, we found that RASSF1A overexpression inhibited signal transmission from Ras to its downstream effector Raf1, which subsequently reduced the activation of the pro-hypertrophic ERK1/2 signalling axis. Furthermore, a significant downregulation of RASSF1A expression by ∼50% was observed in failing human hearts (n=3, p<0.05) strongly indicating its involvement in the development of heart failure. In conclusion, our data establish RASSF1A as a potent inhibitor of cardiac hypertrophy by modulating the Ras-Raf1-ERK1/2 pathway. This may provide opportunities for the development of novel therapeutic strategies for heart failure in the future.